2002
DOI: 10.1111/j.1744-7348.2002.tb00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungitoxic properties of selected South African plant species against plant pathogens of economic importance in agriculture

Abstract: SummaryThirty‐nine plant species, representing 20 families from the subclasses Rosidae, Asteridae, Commelinidae and Liliidae, were collected from the Blyde River Canyon Nature Reserve, Mpumalanga, South Africa. Crude extracts were prepared and bioassayed, at equal concentrations, for their antifungal potential by determining the inhibitory effects on the mycelial growth of seven economically important plant pathogenic fungi. Statistically significant differences between plants and plant parts were observed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…The study in refs. [36,37] has confirmed that the strong antifungal property of semi purified extracts of several plants extracts.…”
Section: Antifungal Assay Antifungal Activity Of Resin (Crude Extractmentioning
confidence: 61%
“…The study in refs. [36,37] has confirmed that the strong antifungal property of semi purified extracts of several plants extracts.…”
Section: Antifungal Assay Antifungal Activity Of Resin (Crude Extractmentioning
confidence: 61%
“…Another problem is that the synthetic fungicides are non-biodegradable; thereby presenting an environmental hazard for human beings, flora and fauna (Hayes and Laws 1991;Latorre et al 1994;Paulitz and Bélanger 2001). As the use of synthetic fungicides is being reduced globally, the search for natural alternatives of phytosanitary control has increased (Waard et al 1993;Pretorius et al 2002). In this context, antifungal properties have been confirmed in crude and semi-purified extracts of several plants (Duke 1990;Pretorius et al 2002;Meepagala et al 2003).…”
Section: Introductionmentioning
confidence: 94%
“…The current international trend is toward banning chemicals too toxic for the environment and human workers and to develop approaches based on biological molecules. In this context the application of crude plant extracts for the control of diseases and pests in crop production systems has the potential to offer a safer and less controversial alternative practice to chemical pesticides (Pretorius et al 2002).…”
Section: Introductionmentioning
confidence: 99%